2020
DOI: 10.3390/molecules25215012
|View full text |Cite
|
Sign up to set email alerts
|

Differential Precipitation of Mg(OH)2 from CaSO4·2H2O Using Citrate as Inhibitor—A Promising Concept for Reagent Recovery from MgSO4 Waste Streams

Abstract: In hydrometallurgical processing and acidic wastewater treatment, one of the neutralizing agents employed is MgO or Mg(OH)2. At the end of this process, the resulting solution, which is rich in SO42− and Mg2+ is treated with lime to remove (or minimize the amount) of these ions via the precipitation of Mg(OH)2 and CaSO4·2H2O (gypsum). In our work, an attempt was made to separate the two solids by increasing the induction time of the gypsum precipitation, thus regenerating relatively pure Mg(OH)2 which could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, there is also no evidence of crystallinity in the BF-TEM images. Further research is needed to conclusively determine if the reaction layer is a crystalline phase or not, but previous studies have observed precipitation of amorphous magnesium hydroxide during reactions between magnesium sulfate and calcium hydroxide, as well as precipitation of amorphous phases during the reaction of MgO in ambient conditions for time periods shorter than 2 months. ,, …”
Section: Resultsmentioning
confidence: 99%
“…However, there is also no evidence of crystallinity in the BF-TEM images. Further research is needed to conclusively determine if the reaction layer is a crystalline phase or not, but previous studies have observed precipitation of amorphous magnesium hydroxide during reactions between magnesium sulfate and calcium hydroxide, as well as precipitation of amorphous phases during the reaction of MgO in ambient conditions for time periods shorter than 2 months. ,, …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the low release of Mg could possibly be because of the precipitation of Mg 2+ in the form of less soluble forms such as Mg(OH) 2 (pK SP = 10.86) (Ziegenheim et al, 2020) at increased Mg 2+ and OH − concentration. Angst and Sohi (2013) in their study to establish K, Mg and P released by biochar noted that both P and Mg were gradually released from biochar suggesting its suitability for use as a slow-release fertilizer.…”
Section: Magnesium (Mg) and Phosphorus (P) Concentrations Of Biocharmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/membranes13060562/s1, Figure S1: Custom-made frame set-up for membrane fabrication through interfacial polymerization, Figure S2: XRD spectra of the product obtained as a result of electrodialysis. References [46,47]…”
Section: Supplementary Materialsmentioning
confidence: 99%